The World Bank Annual Report 2000 : Volume 2. Financial Statements and Appendixes - World Bank (Washington, DC, 2013)
This annual report, which covers the period from July 1, 1999 to June 30, 2000, spells out the guiding principles of the Bank's work: country ownership, long-term integrated approach, partnership, and results focus. This vision was put into practice under a pilot approach, the Comprehensive Development Framework. The following are some of the highlights of Fiscal Year 2000: a) The share of projects at risk of not achieving their development objectives fell to an estimated 15 percent of the total in fiscal 2000, or roughly half the rate of fiscal 1998. b) New lending commitments declined to $15.3 billion. c) Seven countries qualified for debt relief under the enhanced initiative for Heavily Indebted Poor Countries, six of them in Africa. d) The Bank and the International Monetary Fund began to help countries prepare Poverty Reduction Strategies, which are becoming the basis for debt relief and concessional lending by the Bank, the Fund, and other development partners. e) The Bank announced up to $1 billion support to help borrowers of the International Development Association to combat HIV/AIDS, and to address priority social problems with cross-border or global dimensions - with a special focus on Africa, and active partnership in the Global Alliance for Vaccines and Immunization.